Pelatihan Pembuatan Teacher’s Web Blog Pada Guru SMK PGRI 23 Jakarta Selatan - Akbar, Astried Silvanie (Lembaga Penelitian Dan Pengabdian Pada Masyarakat (LPPM) Institut Bisnis dan Informatika (IBI) Kosgoro 1957, 2020)
Web Blog has been used since the raise of web 2.0 for writing content on the Internet. On this community dedication activities, we teach the teachers from SMK PGRI 23 to make an educational blog as part of teaching methods. The main objective of preparing the teachers with enough skills to blogging so they can face all challenges on the fast growth of Internet technology. The e-learning education method with using the blog as a new platform, expected to be an additional media for their current conventional teaching method. The blog platform used was WordPress because it is one of the popular Content Management System for blogging. We teach them practically in the computer lab so they can have hands-on experience directly to use the blog system. The study case is related to their own teaching experience so they can grasp the meaning of education blogging. The result is an education blog publication by each teacher in the public domain wordpress.com. The continuation of the program is suggested by the audience so they can continue the learning process on to the next level.